2017
DOI: 10.11648/j.ajtas.20170602.18
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Spatial Modeling of Acute Respiratory Infections (ARI) Among Children Less Than Five Years in Kenya

Abstract: Abstract:Bayesian disease mapping is a field of statistics that is used to model the spatial distribution of disease outcomes especially in application to studies in spatial biostatistics and also as a tool to help develop the required intervention strategies. In this study, we perform a spatial modeling of ARI among children less than five years in Kenya using data from the 2014 Kenya Demographic and Health Survey (KDHS). Four models were used in this study namely the logistic regression model, the normal uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
1
1
Order By: Relevance
“…Another unexpected finding of this study was that, with an increase in the number of household members, the chances of having ARI among children decreased, contradicting the finding of a study in Kenya and one in Copenhagen, Denmark (Von Linstow et al, 2008;Muthoni, 2017). This might be caused by children in Afghanistan getting more attention and care from household members.…”
Section: Discussioncontrasting
confidence: 85%
“…Another unexpected finding of this study was that, with an increase in the number of household members, the chances of having ARI among children decreased, contradicting the finding of a study in Kenya and one in Copenhagen, Denmark (Von Linstow et al, 2008;Muthoni, 2017). This might be caused by children in Afghanistan getting more attention and care from household members.…”
Section: Discussioncontrasting
confidence: 85%
“…This study reported a prevalence of 59.2%. In agreement with this finding, Muthoni & Ngesa [9], reported an estimated ARI prevalence of 55-60 % for Kwale County from models based on national health and demographic survey data. Additionally, a high individual risk of infection by various respiratory viruses, up to 93.4% was reported in a large household survey in rural North Coast with similar settings [23], suggesting a high likelihood of occurrence of ARIs along the larger coastal region.…”
Section: Discussionsupporting
confidence: 64%
“…Over half of all diagnosis among children presenting with ARI symptoms are usually due to acute upper respiratory tract infections [6,7]. A child can experience up to eight episodes of ARIs of varying severity in a year [8][9][10].…”
Section: Introductionmentioning
confidence: 99%